Crystal structure of (Z)-4-(((4-fluorophenyl)amino)(furan-2-yl)methylene)-5-methyl-2-phenyl-2,4-dihydro-3H-pyrazol-3-one - Wu Qiong; Zhang Li; Gao Jun-Jie; Yang Liu; Zhang Heng-Qiang; Fan Li-Li; Zhang Ya-Zhai (Zeitschrift für Kristallographie - New Crystal Structures)
C22H16FN3O2, triclinic, P1‾$\overline{1}$ (no. 2), a = 8.7335(18) Å, b = 9.967(2) Å, c = 11.968(3) Å, α = 70.677(4)°, β = 86.259(4)°, γ = 65.759(4) Å, V = 893.4(3) Å3, Z = 2, Rgt(F) = 0.0543, wRref (F2) = 0.1677, T = 296(2) K.